Ancestry and genetic associations with bronchopulmonary dysplasia in preterm infants - Torgerson, Dara G. (Am J Physiol Lung Cell Mol Physiol, 2018)
Bronchopulmonary dysplasia in premature infants is a common and often severe lung disease with long-term sequelae. A genetic component is suspected but not fully defined. We performed an ancestry and genome-wide association study to identify variants, genes, and pathways associated with survival without bronchopulmonary dysplasia in 387 high-risk infants treated with inhaled nitric oxide in the Trial of Late Surfactant study. Global African genetic ancestry was associated with increased survival without bronchopulmonary dysplasia among infants of maternal self-reported Hispanic white race/ethnicity [odds ratio (OR) = 4.5, P = 0.01]. Admixture mapping found suggestive outcome associations with local African ancestry at chromosome bands 18q21 and 10q22 among infants of maternal self-reported African-American race/ethnicity. For all infants, the top individual variant identified was within the intron of NBL1, which is expressed in midtrimester lung and is an antagonist of bone morphogenetic proteins (rs372271081, OR = 0.17, P = 7.4 × 10(−7)). The protective allele of this variant was significantly associated with lower nitric oxide metabolites in the urine of non-Hispanic white infants (P = 0.006), supporting a role in the racial differential response to nitric oxide. Interrogating genes upregulated in bronchopulmonary dysplasia lungs indicated association with variants in CCL18, a cytokine associated with fibrosis and interstitial lung disease, and pathway analyses implicated variation in genes involved in immune/inflammatory processes in response to infection and mechanical ventilation. Our results suggest that genetic variation related to lung development, drug metabolism, and immune response contribute to individual and racial/ethnic differences in respiratory outcomes following inhaled nitric oxide treatment of high-risk premature infants.